COUMARINS AND A FLAVONOID FROM PTEROCAULON ALOPECUROIDES - Vilegas, Wagner [UNESP]; Boralle, N.; Cabrera, A.; Bernardi, A. C.; Pozetti, G. L.; Arantes, S. F. (Elsevier B.V., 1995)
From a CH2Cl2 extract of the aerial parts of Pterocaulon alopecuroides, two oxyprenyl coumarins, 7-(2,3-dihydroxy-3-methylbutyloxy)-6-methoxy coumarin and 7-(2,3-dihydroxy-3-methylbutyloxy)-5-hydroxy-6-methoxy coumarin and one flavononol, 3,5,3',4'-tetrahydroxy-7-(2,3-en-3-methylbutyloxy)-2,3-dihydroflavonol, were isolated.
Keywords: PTEROCAULON ALOPECURIODES; COMPOSITAE; COUMARINS; FLAVONOL